Metabolism of alkaline phosphatase and acid phosphatase in goats - V. Sakhniuk; M. Hotsuliak; V. Marchuk; A. Kharchenko; M. Savcheniuk (Regulatory Mechanisms in Biosystems, 2025)
Goat breeding is a branch of world livestock production that has a rich history, modern achievements and gradual develo p ment in different countries of the world due to the widespread introduction of innovative technologies. The purpose of this study was to determine the physiological limits of alkaline and acid phosphatase activity in blood serum, as well as to study the dyna m ics of these parameters in clinically healthy and subclinical hypocalcaemic dairy goats. The subject s of the study w ere pregnant and lactating Zaanen, Alpine and LaMancha goats. The activity of total alkaline phosphatase (ALP) and its bone and intestinal isoenzymes, acid phosphatase (ACP), concentration of total calcium, and ionised calcium were determined in goat serum by standardised methods. The measurements were performed on a Stat Fax 4500+ biochemical analyzer. The physiological limits of the activity of total alkaline phosphatase (12.6–412.2 U/L), its intestinal (5.5–70.5 U/L) and bone isoenzymes (7.3–401.3 U/L), and acid phosphatase (0.92–11.56 U/L) in the blood serum of clinically healthy goats were established. In the subclinical course of hypocalcemia, the activity of ALP in the serum of goats was 266.9 ± 15.1 U/L, which is 1.3 0 times higher than in clinically healthy animals (212.4 ± 11.2 U/L). In particular, the activity of intestinal and bone isoenzymes of ALP in diseased animals was 1.48 and 1.26 times higher compared to clinically healthy goats. The activity of acid phosphatase in the subclinical course of hypocalcemia averaged 9.02 ± 0.48 U/L (0.63–58.80 U/L), which was 1.45 times higher than in clinically healthy animals (6.24 ± 0.26 U/L; 1.00–27.60 U/L) and is evidence of increased resorption in goat bone tissue.